Challenges for Resolution of Banks in Sub-Saharan Africa - Barend Jansen, Jan (World Bank E-Library Archive, 2019)
While the recent global financial crisis has affected many developed countries, it has had less impact in Africa. Nevertheless, the lessons learned from this crisis are relevant for African countries, especially because banking groups with a head office in Africa have grown rapidly and these groups are systemically present in many of their African host countries. As macroeconomic conditions have deteriorated in many Sub-Saharan African countries in the last two years, the question arises whether the regulatory framework for the financial systems of these countries is strong enough to face a serious financial crisis in the future. This paper highlights the twelve essential characteristics of effective resolution regimes for financial institutions, as provided by the Key Attributes. These features should be integrated in the national resolution frameworks for financial institutions and tailored to the local circumstances and legal traditions. For each feature, the paper maps the challenges for introducing them in resolution regimes for banks in the Sub-Saharan African region